On geometric moment invariants - M. Alenezi, Ahmad; Sapar, Siti Hasana; Rakhimov, I.S. (Academic Publications, 2018)
In this paper we study the geometric moments invariants. We describe an image in terms of features which are invariant to some sort of transformations i.e mentioned translation, rotation and scaling change in exposure, brightness etc. Our aim is to check the performance of components for feature vectors.